Design and Implementation of Web-Based Lecture Evaluation System - Winarno Winarno (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
This study aimed to produce a web-based lecture evaluation system in the Post-Graduate Program of IAIN Salatiga. The developed system was called SEVADO (Sistem Evaluasi Perkuliahan Dosen/Evaluation System of the Lecturer’s learning). The method of this research was research and development (R&D). The data collection techniques were documentations, interviews, focus group discussions (FGD), and questionnaires. The research subjects were 10 students during the pilot study and 46 students in the main research. The aspects which was tested includes functionality, usability, reliability, performance and supportability. To test the aspect of reliability and performance, WAPT tools (Web Application Performance Testing) software was applied. The researcher concludes that the web-based lecture evaluation system of the Post-Graduate Program of IAIN Salatiga was feasible. It met the five aspects of system testing: functionality (score 4.2/excellent category), usability (score 4.3/excellent category), supportability (score 4.3/excellent category), performance (97%), and reliability (92%).